On the Way to the (Un)Known? The Ottoman Empire in Travelogues (c. 1450-1900) - Gruber, Doris; Strohmeyer, Arno (Studies on Modern Orient, 2022)
Twenty-two authors from various countries analyze travelogues on the Ottoman Empire between the fifteenth and the nineteenth centuries. The volume discusses questions of perceptions of "otherness", the circulation of knowledge, intermedial relations, gender roles, and explores possibilities and limits of digital analysis.